Simplication of boolean function based on simplification rules - Chin, Kui Fern (Universiti Malaysia Sarawak, UNIMAS, 2003)
This thesis addresses integration of monolithic transformer, which focused on the analysis and modeling of the chip especially at radio frequencies (GHz). The classical network analysis technique is used to derive two-port parameters of the microtransformer. Thus, the equivalent circuit model is obtained through both measurement and simulation with scattering parameters extraction.